Ответы и объяснения

2013-03-29T00:03:02+04:00
1)4ab+a2-2ab+b2//2(a+b)(A-b)=a-b//2(a+b)
2)...*2a//a+b=-a//a+b
3)...+b//b-a=1
ответ:1
2013-03-29T00:10:06+04:00

(2ав    +  а-в     )    ×    +  в         = ( 2ав           +  (а-в)   )   ×  2а          -    в      =     4ав+(а-в)×(а-в)    

а²-в²      2а+2в      а+в          в-а        (а-в)(а+в)      2(а+в)         а+в          а-в            2(а-в)(а+в)

 

×  2а  -    в        =   4ав+а²-2ав+в²     ×    2а       -   в       =  а²+2ав+в²   ×2а    -   в      =   

    а+в      а-в         2(а-в)(а+в)                 а+в         а-в         2(а-в)(а+в)    а+в     а-в

 

=(а+в)²×2а               -  в        =     а        -   в        =   а-в   =1

2(а-в)(а+в)(а+в)         а-в           (а-в)      (а-в)        а-в